Children’s Emotional Development in Single-Parent Families: A Case Study in Kotangan Village Galang District - Rahmadhani S, Ajeng Putri; Sahrul, Sahrul; Simamora, Irma Yusriani (Program Studi Bimbingan dan Konseling, Fakultas Ilmu Pendidikan, Universitas Negeri Medan, 2023)
The phenomenon of single-parent families has been increasing globally and has a significant impact on children’s emotional development, particularly within the socio-cultural context of rural Indonesian communities. This study aims to analyze the emotional development of children in single-parent families, identify the influencing factors, and examine the challenges faced in the parenting process. This research employed a qualitative approach with a case study design. The population consisted of single-parent families in Kotangan Village, Galang District, Deli Serdang Regency, with three families selected through purposive sampling. The research instruments included interview guidelines, observation sheets, and documentation checklists. The procedure involved in-depth interviews, direct observations, and data triangulation to ensure validity and reliability. Data were analyzed using the Miles and Huberman interactive model, which comprised data reduction, data display, and conclusion drawing. The findings revealed that children’s emotional development in single-parent families was influenced by parenting patterns, the psychological condition of mothers, social support, and religious values. The study concludes that religiosity and social environment function as protective factors that foster emotional stability among children in single-parent households. The findings have theoretical and practical implications for developing culturally and spiritually based family support programs. Future studies are recommended to expand the scope and sample diversity to achieve broader generalization.